Reconciling nutritional geometry with classical dietary restriction: Effects of nutrient intake, not calories, on survival and reproduction. Issue 1 (20th November 2018) - Moatt, Joshua P.; Fyfe, Murray A.; Heap, Elizabeth; Mitchell, Luke J. M.; Moon, Fiona; Walling, Craig A.
Abstract: Dietary restriction (DR) is one of the main experimental paradigms to investigate the mechanisms that determine lifespan and aging. Yet, the exact nutritional parameters responsible for DR remain unclear. Recently, the advent of the geometric framework of nutrition (GF) has refocussed interest from calories to dietary macronutrients. However, GF experiments focus on invertebrates, with the importance of macronutrients in vertebrates still widely debated. This has led to the suggestion of a fundamental difference in the mode of action of DR between vertebrates and invertebrates, questioning the suggestion of an evolutionarily conserved mechanism. The use of dietary dilution rather than restriction in GF studies makes comparison with traditional DR studies difficult. Here, using a novel nonmodel vertebrate system (the stickleback fish, Gasterosteus aculeatus ), we test the effect of macronutrient versus calorie intake on key fitness‐related traits, both using the GF and avoiding dietary dilution. We find that the intake of macronutrients rather than calories determines both mortality risk and reproduction. Male mortality risk was lowest on intermediate lipid intakes, and female risk was generally reduced by low protein intakes. The effect of macronutrient intake on reproduction was similar between the sexes, with high protein intakes maximizing reproduction. Our results provide, to our knowledge, the first evidence that macronutrient, not caloric, intake predicts changes in mortality and reproduction in the absence of dietary dilution. This supports the suggestion of evolutionary conservation in the effect of diet on lifespan, but via variation in macronutrient intake rather than calories.